Correlation between Two Evaluation Methods for the Effect of Two Desensitizing Materials: An In Vitro Study - Elashwah, Mahmoud; Elezz, Ahmed Fawzy Abo; Safy, Rehab Khalil (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study was conducted to assess the efficiency of enamel matrix derivative (EMD) on dentin remineralization at two different application times. MATERIALS AND METHODS: Thirty-two human dentin specimens of 1 mm thickness were prepared and randomly divided into two groups according to the treatment material (M) used: fluoride varnish with casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) (M1) and Enamel matrix derivative (EMD) (M2). Following treatment, each group was subdivided into two subgroups (n = 8) based on the storage time in artificial saliva into: (S); subgroup (S1); storage for 15 days and subgroup (S2); storage for 30 days. Dentin permeability was measured for all specimens at baseline and after applying the treatment protocol. All specimens were photomicrographed using ESEM before and after the treatment protocol. RESULTS: The highest permeability reduction percent mean value was recorded for M1S2 specimens (90% ± 20), with a statistically significant difference with other subgroups, followed by subgroup M2S2 (56% ± 8) and subgroup M1S1 (51% ± 11), respectively. Meanwhile, the subgroup M2S1 had the lowest mean value (36% ± 9). In addition, the dentin permeability test was confirmed by the ESEM results. CONCLUSION: EMD could be used as a promising remineralizing agent for dentin remineralization.